IMPROVING SPEAKING SKILLS THROUGH SPEECH ACTIVITY OF ENGLISH CLUB AT DARUNNAJAH BOARDING SCHOOL: IMPROVING SPEAKING SKILLS THROUGH SPEECH ACTIVITY OF ENGLISH CLUB AT DARUNNAJAH BOARDING SCHOOL - Lisan, Khusnul; Subir (CV. Mitkom Indotama, 2024)
ABSTRACT The abstract aimed at improving speaking skills through speech activity of English Club since speaking was still considered as the hardest skill in the place. This research was conducted using Classroom Action Research (CAR). There were 60 students as research subjects, 40 females, and 20 males. They were the students of Darunnajah Boarding school. This research was conducted in two cycles, each consisted of planning, implementation, observation, and reflection. Data were collected through quantitative in the form of test and qualitative data in the form of observation and interview. The results of this study indicated that there was an increase in students' speaking skills. This was proved with result of student test from cycles 1 to 2. This showed that the scores and averages in the second cycle were better than the first cycle. The percentage of students who got points >75 also increased. In the pre-test students who got points >75 and above were 9 students (15%). In the post-test of cycle, I students who scored >75 and above were 20 students (33%). In the post-test of cycle II, there were 52 students (86%) who got score more than >75. In other words, students' speaking ability increased and became better after implementing speech technique.